CRITICAL ANALYSIS OF PAYMENT DELAYS, UNDER-PAYMENTS AND NON-PAYMENTS ENCUMBERING ENGINEERING CONSULTANCY PRACTICES IN CONSTRUCTION PROJECTS - Ting, Sim Nee; Lee, Yee Yong; Gui, Hun Chuen; Chong, Wan Siang; Ng, Chee Khoon (Malaysian Institute of Planners, 2026)
Engineering Consultancy Practice (ECP) plays a crucial role in Malaysia's construction industry, supporting the nation development and progress. Engineering consultants through their professional practices provide essential technical services and expert advice to clients throughout construction projects. In Malaysia, consultants are typically reimbursed based on the Board of Engineers Malaysia (BEM) Scale of Fees, which serves as the primary revenue source sustaining ECP operations. However, despite the adherence to BEM's Scale of Fees, engineering consultants in Malaysia continuously encounter payment issues, namely payment delays, under-payment and even non-payment, posing a concerning scenario within the nation's construction industry. To determine the extent and significance of payment issues affecting engineering consultants, this study employed a structured questionnaires survey targeting engineering consultants in Malaysia. A total of 174 responses were collected through online questionnaires, telephone interviews, face-to-face engagement and email correspondence. The findings show that late payment, underpayment and non-payment are prevalent across government, GLC and private projects, with the private sector recording the greatest incidence, delays averaging one to three months, and typical payment deficits of 10–30%. The study contributes empirical benchmarks that support more effective contractual, regulatory and payment management frameworks to strengthen financial sustainability within engineering consultancy practice.